2019
DOI: 10.1038/s41598-019-39792-0
|View full text |Cite
|
Sign up to set email alerts
|

Ecological analysis of Kashin-Beck osteoarthropathy risk factors in Tibet’s Qamdo City, China

Abstract: We studied Tibet’s Qamdo City, which currently hosts the most serious prevalence of Kashin-Beck osteoarthropathy (KB) in China. This study utilizes the geographical detector (GeoDetector) algorithm to measure the individual and interactive influences of risk factors on KB and to quantify the highest potential risk subzones of each principal factor. With a comprehensive consideration of 13 possible related factors, namely, the tectonic division, stratum, moisture index, gross domestic product, mean annual preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
(32 reference statements)
1
15
0
Order By: Relevance
“…The relationship between KBD and selenium (Se) has always been a hot topic in the environmental etiology of KBD. Numerous studies have demonstrated that the prevalence of KBD is closely related to the low Se environment [12][13][14][15][16][17], and Se supplementation can effectively control and prevent KBD [18][19][20][21]. Nevertheless, there were still some studies questioning this Se deficiency etiological hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between KBD and selenium (Se) has always been a hot topic in the environmental etiology of KBD. Numerous studies have demonstrated that the prevalence of KBD is closely related to the low Se environment [12][13][14][15][16][17], and Se supplementation can effectively control and prevent KBD [18][19][20][21]. Nevertheless, there were still some studies questioning this Se deficiency etiological hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…The first cases of Keshan disease (KD) were discovered over 80 years ago in Keshan County (Heilongjiang Province, north-eastern China) [ 60 ]. The disease was characterized by congestive cardiomyopathy and affected children aged 2–7 years and women of reproductive age [ 61 ], whereas Kashin-Beck disease (KBD) occurs most frequently in Tibet [ 62 ] and begins in childhood around age five [ 63 , 64 ]. KBD is characterized by osteoarthritis, leading to the degradation of cartilage in the upper and lower limbs [ 63 ].…”
Section: Dietary Intake Of Seleniummentioning
confidence: 99%
“…The health loss of KBD is directly related to the severity of KBD. Selenium (Se) deficiency is acknowledged as an important environmental risk factor for the onset of KBD [ 3 , 13 , 14 ]. A great number of studies have reported the close link between the prevalence of KBD and low-Se environment [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%